Kemampuan membaca pemahaman siswa kelas IV SD berdasarkan tes internasional dan tes lokal - Basuki, Imam Agus (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This article is aimed at elaborating not only students’ reading comprehension based on international and local tests conducted for fourth-grade elementary school students, but also the correlation between both results. This descriptive research was conducted at 12 elementary schools in five provinces located in Java and Sumatra. The instruments used for the reading comprehension tests were PIRLS, an international test, and a researcher-made test. The results of the study show that fourth graders’ ability to comprehend texts is very low. They could only understand 30% of the reading texts, both informative and literary. The results of the international test show a very high correlation with those of the researcher-made test, although they indicate lower scores than the local test results.